2008
DOI: 10.1111/j.1572-0241.2008.01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for Upper and Lower GI Events Associated With Traditional NSAIDs and Acetaminophen Among the Elderly in Quebec, Canada

Abstract: Among elderly patients requiring analgesic/anti-inflammatory treatment, use of the combination of a tNSAID and acetaminophen may increase the risk of GI bleeding compared with either agent alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
2
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 27 publications
4
67
2
9
Order By: Relevance
“…With the use of published methodology, 5 exposure was defined to be 1.25×(number of days supplied) to extend exposure by a conservative grace period during which pharmacologically induced GI bleeding may occur. An individual would be considered off the CAT regimen, ie, time periods with no exposure, when that individual's longitudinal prescription-fill data did not demonstrate prescription of the drugs of interest.…”
Section: Assessment Of Drug Exposurementioning
confidence: 99%
“…With the use of published methodology, 5 exposure was defined to be 1.25×(number of days supplied) to extend exposure by a conservative grace period during which pharmacologically induced GI bleeding may occur. An individual would be considered off the CAT regimen, ie, time periods with no exposure, when that individual's longitudinal prescription-fill data did not demonstrate prescription of the drugs of interest.…”
Section: Assessment Of Drug Exposurementioning
confidence: 99%
“…In our case, the finding of nonspecific inflammation in the cecum and ileocecal valve was thought to be related with the chronic usage of nonsteroidal antiinflammatory drugs (NSAIDs) over the previous year, because of the chronic abdominal pain. NSAIDs may lead to mucosal ulcerations, increased mucosal permeability and inflammation in the lower gastrointestinal tract (17). An autopsy study of more than 700 cases revealed that 8.4% of the chronic NSAID users had small bowel ulcers, while this ratio was 0.06% in nonusers (18).…”
Section: Discussionmentioning
confidence: 99%
“…Otuz günlük tekrar kanama inisiyal endoskopik hemostazda baflar›s›zl›k ve ciddi ko-morbidite ile iliflkili bulunmufltur (13). Ko-morbidite ile mortalite aras›ndaki iliflki di¤er çal›flmalarda da gösteril-mifltir (14,15).…”
Section: G‹r‹fiunclassified